Meritocracy Moderating the Influence of Person Job Fit and Career Development on Affective Commitment - Fatia Maulida; Mf.Arrozi Adhikara; Rina Anindita (Global Management: International Journal of Management Science and Entrepreneurship, 2026)
Background: In the competitive healthcare landscape, where human resources are pivotal to organizational success, affective commitment defined as emotional attachment to the workplace is essential for nurse retention and service quality. Satya Negara Hospital in North Jakarta exemplifies the challenges faced by Indonesian healthcare institutions, with a notably high nurse turnover intention of 30% in 2024, signaling low affective commitment and underscoring the urgency to identify its drivers. While person-job fit and career development are established antecedents of commitment, their combined influence within Indonesia’s nursing context, along with the potential moderating role of meritocracy, remains underexplored.. Methods:  Using a quantitative, cross sectional design, data were collected via a validated questionnaire from all 108 nurses at the hospital and analyzed using multiple regression.. Results: The results revealed that person-job fit, career development, and meritocracy collectively explain 96.6% of the variance in affective commitment. Furthermore, when meritocracy was tested as a moderating variable, the explanatory power of the model increased significantly, with the adjusted R² value rising from 96.6% to 98.5%. This indicates that the presence of a meritocratic system substantially amplifies the positive effects of both person-job fit and career development on commitment.. Conclusion: The study concludes that a synergistic combination of job fit, growth opportunities, and a merit-based system is fundamental to fostering nurses’ emotional attachment. These findings contribute to organizational and psychological theory integration and offer practical human resource strategies for enhancing nurse commitment and reducing turnover in healthcare settings.